GEOCHEMICAL MODEL OF THE FORMATION OF THE SPOKOININSK TUNGSTEN DEPOSIT (EASTERN TRANSBAIKAL REGION, RUSSIA) - Matveeva S.S.; Spasennykh M.Yu.; Sushchevskaya T.M.; Bychkov A.Yu.; Ignat'ev A.V. (My University, 2002)
This article reviews data on the geological structure and chemical compositions of the main rock varieties and typomorphic minerals (muscovites and wolframites) at the Spokoininsk greisen tungsten deposit. The fluid regime is characterized by the following data on fluid inclusions in minerals: the determination of gas and salt compositions, including the composition of a number of ore elements, and evaluation of the redox potential. The data on the isotope compositions (H, C, and O) of mineral-forming solutions was based on the isotope compositions of the hydrogen of muscovites, oxygen of quartz, and carbon of C02 in fluid inclusions. The oxygen isotope compositions of rocks, formed at the interaction of the ascending magmatic fluid with granites, were used for the elaboration of a model of vertical zonality. Regularities in changes of REE spectra were studied for rock and mineral carriers of lanthanoids (wolframites and fluorites). The proposed model of the formation of the Spokoininsk deposit, attributed to the type of mineralized cupolas, was based on geological and geochemical information. The deposit was formed by magmatogene fluids; any evidences of mixing with waters of other origin are lacking. The initial homogenous fluids, ascending from deep-seated zones of the magmatic chamber, became heterogenized due to a gradual temperature drop. The filtration of a two-phase fluid into highly permeable media led to a hydrodynamic phase separation with the enrichment of the frontal parts of fluid flows with the gas phase. The phase separation during the filtration resulted in a shift in the chemical equilibrium in the solution-rock system. This led to a metasomatic transformation of granites, the degree of which increased towards the peak of a granitic stock. The deposition of the main amount of wolframite was related to this process. The ore process was completed with the formation of wolframite-quartz veins. In this case. fluids were also heterogenized, while conditions for the phase separation were lacking.